Ab initio study of pressure-dependent phonon heat conduction in cubic boron nitride. (July 2023) - Wu, Jing; Zhang, Hao; Wang, Tianyu; Qian, Xin; Song, Bai; Liu, Te-Huan; Yang, Ronggui
Highlights: Pressure-enhanced phonon conduction was studied for four isotopic c -BNs. The suppression of the aao process is mainly responsible for the enhanced κ . When pressure is applied, the contribution of TA phonons to κ can increase more. The thermal transport of isotopically enriched c -BN is less sensitive to pressure. Abstract: Phonon transport in cubic boron nitride ( c -BN) at elevated pressure in several tens GPa is potentially of interest for cooling high-power electronics. In this work, we study the pressure-dependent thermal conductivity (up to 20 GPa) of isotope-engineered c -BN by solving the Boltzmann transport equation with inputs only from ab initio calculations. Four boron isotope compositions are analyzed, including natural abundance, enriched 10 B and 11 B, and a roughly equal mixture of the two. In all cases, the thermal conductivity of c -BN increases linearly with pressure. Compared to isotope-enriched c -BN, the thermal conductivity of isotopically mixed c -BN is less sensitive to pressure variations since phonon-isotope scattering causes substantial thermal resistance yet is pressure independent. Based on mode-resolved analysis, the thermal conductivity enhancement is mainly attributed to the suppression of the aao absorption processes with transverse-acoustic phonons in the frequency range from 300 to 600 cm –1, due to the synergistic effect between decreased coupling strength and phonon hardening. In addition, suppression of the aaa processes is also responsible for a slight increase in thermal conductivity. Our results are further supported by the frequency- and mean-free-path-dependent spectra of the thermal conductivity. This work provided a fundamental interpretation of pressure-dependent phonon transport in c -BN from a microscopic perspective.